Monitoring of Combined Mechanical Injury - Evans Z. Morgan, Jacob E. Christopher, Priya F. Davies (Academic Journal of Clinicians, 2024)
Combined mechanical injury refers to the simultaneous occurrence of multiple types of mechanical trauma, such as blunt force trauma, fractures, and lacerations, resulting in complex and challenging clinical scenarios. This structured abstract aims to provide an overview of the monitoring strategies employed in the management of combined mechanical injury. Effective monitoring plays a crucial role in the timely detection and management of combined mechanical injury. Continuous vital signs monitoring, including heart rate, blood pressure, and oxygen saturation, forms the foundation of patient assessment, enabling prompt identification of changes indicative of deteriorating condition or internal injuries. In addition to vital signs, various diagnostic tools are employed to monitor specific aspects of combined mechanical injury. Imaging modalities, such as X-ray, computed tomography (CT), and ultrasound, aid in the identification and characterization of fractures, internal bleeding, or organ damage. Serial laboratory tests, including complete blood count, coagulation profiles, and biomarker analysis, help assess systemic response, detect infection, and monitor organ function. Emerging technologies, such as remote monitoring systems and wearable sensors, offer potential advancements in the monitoring of combined mechanical injury. These technologies provide real-time data collection, allowing for continuous monitoring outside of clinical settings and enhancing early detection of complications or changes in patient condition